Management of benign bone tumours. Issue 3 (June 2017) - Perera, Jonathan R.; Saifuddin, Asif; Pollock, Rob
Abstract: Benign bone tumours are rare, occurring most commonly in skeletally immature patients, and usually arising from cartilage or bone. The commonest locations are the distal femur, proximal tibia and proximal humerus. They present with pain, swelling or pathological fracture. Diagnosis is by plain radiographs, MRI and core needle biopsy if indicated. More aggressive tumours may appear radiologically similar to malignant tumours. Management depends upon anatomical location, symptoms, morbidity of treatment and the natural history of the tumour. In most cases it involves either simple excision or curettage, although occasionally it is necessary to perform a complete excision using the same principles as for malignant tumours.